Systematic Literature Review: An exploration of teacher competencies in inclusion education - Liswandari, Ajeng Linda (Universitas Riau Kepulauan, 2024)
This research examines the exploration of teacher competency in inclusive education which can be identified through pedagogical, professional, social and personality competencies. This research uses Systematic Literature Review (SLR) to identify, review and evaluate several studies that are relevant in answering the problem statements. Moreover, research with SLR method has several stages from formulating questions, searching for literature, determining the indicators, examining the literature, presenting, processing and drawing conclusions from the data obtained. Based on literature review, the researchers found 15 articles and reselected it into 9 articles. Then, researchers compare the findings and draw conclusions from these results. From the research result, it was found that competency becomes a media for providing the best learning quality for student’s satisfaction in teaching and learning process. This proficiency is critical because it allows teachers to fulfill their roles as facilitators, motivators, inspirers, learning guides, and resources for students rather than being ordinary teaching agents that only acts as learning source for their students.